Proceedings of the twentieth anniversary seminar on development of fish products in Southeast Asia : (Southeast Asian Fisheries Development center, 1988)
This purpose was to provide a forum for an updated exchange of information on the status of post harvest technology, to discuss common problems, to shre experience and to make recommendations for action